2010
DOI: 10.1371/journal.pone.0014399
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1-S6K Activation by Endotoxin Contributes to Cytokine Up-Regulation and Early Lethality in Animals

Abstract: BackgroundmTORC1 (mammalian target of rapamycin complex 1) activation has been demonstrated in response to endotoxin challenge, but the mechanism and significance are unclear. We investigated the effect of mTORC1 suppression in an animal model of endotoxemia and in a cellular model of endotoxin signaling.Methodology/Principal FindingsMice were treated with the mTORC1 inhibitor rapamycin or vehicle prior to lethal endotoxin challenge. Mortality and cytokine levels were assessed. Cultured macrophage-like cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…In the present study, in addition to measuring the early effects of LPS on brain cytokine levels, we have also demonstrated that LPS can activate the mTOR pathway in several brain areas (Cao et al, 2013;Lee et al, 2010) and for the first time, we have demonstrated that such activation is linked to a regulation of at least two important upstream regulators of mTORC-1, AMPK and AKT. Briefly, AKT phosphorylation is generally considered to increase mTOR activity through the TSC complex (Chong et al, 2012;Russo et al, 2012a); however, AKT can inhibit mTORC-1 complex activity by phosphorylating PRAS40 (proline-rich AKT substrate of 40 kDa), Fig.…”
Section: Lps Mtor Cytokines and Neuroinflammationsupporting
confidence: 58%
See 1 more Smart Citation
“…In the present study, in addition to measuring the early effects of LPS on brain cytokine levels, we have also demonstrated that LPS can activate the mTOR pathway in several brain areas (Cao et al, 2013;Lee et al, 2010) and for the first time, we have demonstrated that such activation is linked to a regulation of at least two important upstream regulators of mTORC-1, AMPK and AKT. Briefly, AKT phosphorylation is generally considered to increase mTOR activity through the TSC complex (Chong et al, 2012;Russo et al, 2012a); however, AKT can inhibit mTORC-1 complex activity by phosphorylating PRAS40 (proline-rich AKT substrate of 40 kDa), Fig.…”
Section: Lps Mtor Cytokines and Neuroinflammationsupporting
confidence: 58%
“…Effects of LPS and RAP on downstream mTOR activity measured by p-mTOR and p-p70S6K levels p70 ribosomal protein S6 kinase (p70S6K) represents the best characterized downstream kinase target of mTOR activity (Russo et al, 2012a). To test for the possible activation of this pathway by LPS and its modulation by RAP in our experiments (Lee et al, 2010), we quantified the effects of both drugs alone and in combination, by Western blot (WB) analysis of the phosphorylated products phospho-mTOR (p-mTOR) and phospho-p70S6K (p-p70S6K) in the brain of WAG/Rij rats (n = 5 for each treatment-group and time point). We found that RAP (0.5 mg/kg) administered alone had no effects on the amount of p-mTOR expressed in the cortex, hippocampus or thalamus (relative to control untreated WAG/Rij rats), up to 90 min after drug administration ( Fig.…”
Section: Effects Of Lps and Rap Co-administration On Absence Seizuresmentioning
confidence: 99%
“…In contrast, AKT1 KO and ROCK2 KO cells exhibited no apparent change in either KCC3 P-Thr 991 /Thr 1048 or NKCC1 P-Thr 203 /Thr 207 /Thr 212 . Moreover, TSC1 KO and TSC2 KO cells (containing reduced levels of activated AKT1 and SGK131323334, showed apparently increased levels of KCC3 P-Thr 991 /Thr 1048 (>1.3-2 fold, p  <  0.05 ; Fig. 2C and Supplementary Figure 2B).…”
Section: Resultsmentioning
confidence: 93%
“…To identify kinases that might directly phosphorylate KCC3, we limited the tertiary (validation) screen to only serine-threonine kinases. We examined KCC3 P-Thr 991 using phospho-antibodies in cell lines knocked out for WNK3, PRKD1 (i.e., encoding Protein Kinase D1 [PKD1], also known as PKC-Mu), AKT1, ROCK2, and TSC1 and TSC2 (as models harboring significantly decreased AKT1 and SGK1 activity31323334. KCC3 P-Thr 1048 and NKCC1 P-Thr 203 /Thr 207 /Thr 212 were also monitored with phospho-antibodies2428 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because any therapeutic approach for patients with ADPKD would be relevant only for adult patients, we next tested the ability of FC-rapa to inhibit mTOR pathway activity in different tissues in adult mice. Since mTOR activity is typically low in most normal adult tissues, we used short-term LPS treatment 32 as a method to stimulate mTOR activity (Supplemental Figure 5). Animals were pretreated with different doses of FC-rapa or unconjugated rapamycin, followed by short-term LPS treatment.…”
Section: Establishment Of An Effective and Tissue-specific Dose Of Fcmentioning
confidence: 99%